Design of Electronic Learning Courses for IT Students Considering the Dominant Learning Style - Morze, Nataliia V.; Glazunova, Olena G. (Information and Communication Technologies in Education, Research, and Industrial Applications, 2014)
Methods of using e-learning courses to support learning activities of students at higher educational institutions are the subject of a large number of scientific and educational studies. In particular, much attention is paid to the structure, content, and format of educational resources of e-learning courses. However, the problem of dependency of their efficiency on the learning styles of students still needs to be further researched. This paper deals with the learning styles characteristic for IT students on the basis of determining their leading modality, designs the structure of e-learning courses for IT students considering the dominating learning styles, and provides the results of pedagogical experiment by measuring the performance and satisfaction in learning activity.